i KEPUASAN PENGUNJUNG KE OBJEK WISATA LEMBAH HARAU KABUPATEN LIMAPULUH KOTA - Rahman, Faizir; Yuliana, Yuliana; Suyuthie, Hijriyantomi (Journal of Home Economics and Tourism, 2017)
This research aims to determine the stisfaction of visitor to the Harau Valley Tourism object of Limapuluh Kota which are measure by five indicators of visitor satisfaction (1) the expectation of the visitor, (2) the fulfillment of the needs of the visitor desire, (3) the desire to use the product again, (4) and the desire to recommend the service to others. The type of this research is descriptive quantitative with population is all visitor who are visiting the Harau Valley Tourism Limapuluh Kota with an average number of visitors per month as many as 21.666 people. Sampling technique in this research is puposive sampling counted 100 people. Data collection technique is done by spreading the questuinnaire using Likert scale and has been tested the validity and reliability. The result showed that overall satisfaction of visitors to Harau Vellay Tourism District Limapuluh Kota are to categorized as quite agree by 60%, and 39% with the interpretation states less agree and 1% states disagree.Keywords: visitor satisfaction, Harau Valley of Limapuluh Kota Regency